Day 4 Wed, December 09, 2015 2015
DOI: 10.2523/iptc-18401-ms
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Potential Formation Damage Mechanisms Associated with Hydraulic Fracturing

Abstract: Hydraulic fracturing technique, using water-soluble polymers, has been extensively used to improve the productivity of oil and gas wells, especially in low-permeability formations. However, the production enhancement by hydraulic fracturing can be hindered by the fracture conductivity damage and/or fracture face skin. This paper describes an approach to establish a suitable fracturing fluid cleanup process by analyzing the performance of different gel breaker types, especially in sours environments. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…In another study conducted on the same fracturing fluids used in this experiment, has shown that during the breaker treatment, the degradation of polymer increases with time. This shows that the breaker used in fracturing fluid was effective in breaking the polymer of the raw samples as per the laboratory test (Almubarak et al 2015). This needed to be confirmed with field fracturing fluid samples.…”
Section: Laboratory Analysis Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In another study conducted on the same fracturing fluids used in this experiment, has shown that during the breaker treatment, the degradation of polymer increases with time. This shows that the breaker used in fracturing fluid was effective in breaking the polymer of the raw samples as per the laboratory test (Almubarak et al 2015). This needed to be confirmed with field fracturing fluid samples.…”
Section: Laboratory Analysis Resultsmentioning
confidence: 81%
“…Further to the flowback fluids analyses, an investigation of the factors that affect the cleanup performance was performed with the aid of PBU and a recently published laboratory work on the fracturing fluids used in the three treatments here (Almubarak et al 2015). It is found that the main factor greatly affecting fracture cleanup effectiveness is reservoir properties.…”
Section: Factors Affecting Cleanup Performancementioning
confidence: 99%
See 1 more Smart Citation
“…To create long cracks, the fracturing fluid must settle gradually enough to carry the proppant. Low fluid loss, minimal pressure losses during transport via the tubing and fractures, and the ability to continue the flow after proppant placement are all necessary. , In addition, it needs to be suitable for use with formation fluids . In order to prevent any screenout during the treatment, it is also crucial that the fluid is resistant to shear and heat .…”
Section: Introductionmentioning
confidence: 99%
“…Reservoir formation damage can result in substantial production capacity and economic loss; hence, understanding the underlying mechanisms of damages and then implementing corresponding protective measures on the target reservoir formation layer with low permeability so as to minimize the formation damage have very important significance for the construction of productivity and the discovery of target formations. …”
Section: Introductionmentioning
confidence: 99%